The Relationship Between Severe Preeclampsia and the Incidence of Small for Gestational Age (SGA) Babies at Fatimah Lamongan Hospital - Rafi Abhipraya Nurlistyo; Eko Nur Sucahyo; Irma Kartikasari; Rewina Intan Asmarani (MESINA (Medical Scientific Journal), 2026)
Babies born weighing less than the 10th percentile for their gestational age are considered Small for Gestational Age (SGA), which increases the risk of health problems and death. Preeclampsia, a condition marked by high blood pressure after 20 weeks of pregnancy, is linked to SGA by reducing blood flow to the placenta, affecting the baby's growth. This study aimed to explore the relationship between preeclampsia and SGA infants at Fatimah General Hospital in Lamongan using observational analysis with a cross-sectional approach. The study included mothers with certain medical records from January to December 2024. Out of 1,536 mothers, 239 had preeclampsia, and 242 infants were SGA. The majority of babies from mothers with preeclampsia were SGA, compared to those without preeclampsia. The study found a strong connection between preeclampsia and SGA and highlighted the need for better education for pregnant women, regular check-ups, and improved teamwork among healthcare providers to manage high-risk pregnancies.